The Little BIG Things: 163 Ways to Pursue EXCELLENCE - Tom Peters (New York Harper Business, 2010)
Business uber-guru Tom Peters is back with his first book in a decade, The Little Big Things. In this age of economic recession and financial uncertainty, the patented Peters approach to business and management-no-nonsense, witty, down-to-earth, insightful-is more pertinent now than ever. As essential for small-business owners as it is for the heads of major corporations, The Little Big Things is a rousing call-to-arms to American business to get "back to the basics" of running a successful enterprise.
Keywords: Business; Nonfiction; Self Help; Leadership; Personal Development; Management; Psychology; Industrial management; Excellence; HRM: Contemporary Issues (HRM2074-N); Global Citizenship (BIN1064-N)